Kajian Pemanfaatan Media Interaktif Berbasis ICT dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Istikhomah; Hasibuan, Madu Madonna Uli; islaminur, Alpina; Kamal, Mugni Fitria; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This study aims to analyze the application of interactive media based on Information and Communication Technology (ICT) in Arabic language learning at Madrasah Ibtidaiyah. The method employed is a literature review, examining various relevant studies and research findings. The results indicate that the use of interactive media such as Wordwall, iSpring, and Canva Edu can enhance students’ interest, motivation, and learning outcomes. These tools support the balanced and enjoyable development of listening, speaking, reading, and writing skills. Furthermore, the teacher’s role shifts toward that of a facilitator, guiding students in active learning. Nevertheless, the implementation of ICT still encounters challenges, including limited facilities and teachers’ digital competencies. Training and policy support are therefore required to ensure that the use of interactive media can be optimized and sustained. This study contributes to the development of ICT-based Islamic education literature and provides direction for innovative 21st-century learning in Madrasah Ibtidaiyah.